Model Penyebaran Rumor di Media Sosial - Tasya Salsabilla Harista; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2023)
Rumors are information that spreads widely without any confirmation of truth and definite facts. One of the media that is used in rumors spreading is social media. The negative impact raised by rumors spreading through social media is the disruption of social stability, economic systems, and politics. The research purpose is to analyze the rumor spreading model on social media. This research is basic research (theoretical) using descriptive methods. The analytical results are obtained of a rumor-free equilibrium point and a rumor spread equilibrium point, each of which is asymptotic stable. The basic reproduction number obtained by the rumor will spread if the rate of movement of the population of individual who never hear the rumor or counter-rumor increases and became a individual who have been exposed to the rumor or counter-rumor.